Water supply of the Tapalpa forestry watershed in Jalisco, focused to environmental services provision - Benavides-Solorio, Juan de D.; González-Guillén, Manuel de J.; López-Paniagua, Cristopher; Valdez-Lazalde, J. René (Instituto de Ecología, A.C., 2016)
In order to assess the feasibility of creating a water market in the Tapalpa, Jalisco, Mexico watershed, the SWAT model was fitted to obtain the watershed water balance. The model was calibrated in one of the five subwatersheds included in the Tapalpa watershed with a good fit (R2 = 0,85). All five forestry subwatersheds had good hydrologic behavior, allowing high infiltration water rates, which later on emerges as surface runoff with low sediment yields. The subwatersheds with high percentage of agriculture and grasslands yield more surface runoff as well as more sediment yields. The evapotranspiration from the forestry subwatersheds were higher than agricultural subwatersheds. The water supply from the Tapalpa watershed is 42’963,900 m3 per year on average.